2017
DOI: 10.1016/j.addbeh.2017.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of smoking cessation group treatment engagement among veterans with serious mental illness

Abstract: High prevalence rates of tobacco use, particularly cigarettes, pose a serious health threat for individuals with serious mental illness (SMI), and research has demonstrated the effectiveness of pharmacotherapy and psychosocial interventions to reduce tobacco use in this group. However, few studies have considered predictors of tobacco cessation treatment engagement among individuals with SMI. The current study examined predictors of engagement in smoking cessation groups among veterans with SMI engaged in ment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…As one of the most powerful predictors of behavior (Rimal & Adkins, 2003), self-efficacy (Bandura, 1997) has demonstrated broad utility in health communication models and research in predicting a range of health behaviors (Bartle & Harvey, 2017;Lee & Park, 2016;Loton & Waters, 2017;Thrasher et al, 2016;Travaglini et al, 2017). This study extends that work into a new domain and proposes the construct of protective efficacy, which shifts the behavioral focus from the self to a dependent other.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…As one of the most powerful predictors of behavior (Rimal & Adkins, 2003), self-efficacy (Bandura, 1997) has demonstrated broad utility in health communication models and research in predicting a range of health behaviors (Bartle & Harvey, 2017;Lee & Park, 2016;Loton & Waters, 2017;Thrasher et al, 2016;Travaglini et al, 2017). This study extends that work into a new domain and proposes the construct of protective efficacy, which shifts the behavioral focus from the self to a dependent other.…”
Section: Discussionmentioning
confidence: 81%
“…Self-efficacy is operationalized as the individual assessment of behavioral and cognitive ability to perform a goal behavior or complete a task. As one of the most powerful predictors of human behavior (Rimal & Adkins, 2003), self-efficacy has been used to understand health behaviors such as smoking cessation (Thrasher et al, 2016;Travaglini et al, 2017), infant feeding (Bartle & Harvey, 2017), psychological distress (Loton & Waters, 2017), fruit consumption (Leung et al, 2017), indoor tanning (Mays & Evans, 2017), and pandemic flu (Lee & Park, 2016).…”
Section: Self-efficacymentioning
confidence: 99%
“…Few if any prior studies have examined whether particular psychiatric diagnoses influence smoking cessation treatment engagement. However, a study of engagement among smokers with serious mental illness found those with more severe symptoms were less likely to attend treatment (Travaglini, Li, Brown, Bennett, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research conducted on the general and psychiatric populations has found several factors associated with the effectiveness of and engagement in tobacco/nicotine cessation efforts. Treatment engagement is positively associated with older age (Cupertino et al, 2007; Khara, Okoli, Nagarajan, Aziz, & Hanley, 2015; Richards et al, 2014), higher education (Cupertino et al, 2007), healthcare coverage (Cupertino et al, 2007; Richards et al, 2014), unemployment (Lee, Hayes, McQuaid, & Borrelli, 2010), severity of mental illness‐related symptoms (Lee et al, 2010; MacPherson, Stipelman, Duplinsky, Brown, & Lejuez, 2008; Richards et al, 2014); history of substance use (Richards et al, 2014); general health (Khara et al, 2015); previous smoking treatment use (Travaglini, Li, Brown, & Bennett, 2017); and late onset of smoking (Aschbrenner, Ferron, Mueser, Bartels, & Brunette, 2015; Khara et al, 2015; Lee et al, 2010; Trainor & Leavey, 2016; Travaglini et al, 2017). These other potential factors (e.g., comorbidity with another mental illness) should be taken into consideration when examining and comparing the probability of remission from nicotine dependence among people with SMI by type of help/services received for tobacco/nicotine use.…”
Section: Introductionmentioning
confidence: 99%